PENGARUH GAYA HIDUP, LABEL HALAL DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN KOSMETIK SOPHIE PARIS PADA MEMBER JARINGAN BISNIS CENTER SUGENG BUDHI HANDOYO AREA CILACAP - Jayanti, Esih; Fatmawati, Siti (JAB (Jurnal Akuntansi & Bisnis), 2020)
This study aims to: Lifestyle, Halal Labels and Prices on Purchasing Decisions of Sophie Paris Cosmetics for Sophie Paris members of the Sugeng Budhi Handoyo Business Center network in the Cilacap area. The population in this study was all Sophie Paris Leader rank members in the Cilacap area who consumed Sophie Paris cosmetics. The method used in this research is quantitative methods. The sample used in this study was 50 people. The data collection technique in this research is a questionnaire, data processing using SPSS for windows version 24.0. The results showed that: there was no influence of Lifestyle on the Purchase Decision of Sophie Paris cosmetics on the members of the Sugeng Budhi Handoyo Business Center network in the Cilacap area, there was a positive effect of the Halal Label on the Purchase Decision of Sophie Paris cosmetics in the Sugeng Budhi Handoyo Business Center network in the Cilacap area, there was no The influence of Price on the Purchase Decision of Sophie Paris cosmetics in the Sugeng Budhi Handoyo Business Center network in the Cilacap area, there is a simultaneous influence of Lifestyle, Halal Label and Price, on the Purchase Decision of Sophie Paris cosmetics on members of the Sugeng Budhi Handoyo Cilacap Business Center network.Â Keyword: Lifestyle, Halal Label, Price, Purchase Decision.